Effects of Alkyl Spacer Length in Carbazole‐Based Self‐Assembled Monolayer Materials on Molecular Conformation and Organic Solar Cell Performance - Qiaonan Chen; Kangbo Sun; Leandro R. Franco; Jingnan Wu; Lars Öhrström; Xianjie Liu; Maureen Gumbo; Mailde S. Ozório; C. Moyses Araujo; Guangye Zhang; André Johansson; Ellen Moons; et al. (Advanced Science)
Abstract Carbazole‐based self‐assembled monolayer (SAM) materials as hole transport layers (HTL) have led organic solar cells (OSCs) to state‐of‐the‐art photovoltaic performance. Nonetheless, the impact of the alkyl spacer length of SAMs remains inadequately understood. To improve the knowledge, four dichloride‐substituted carbazole‐based SAMs (from 2Cl‐2PACz to 2Cl‐5PACz) with spacer lengths of 2–5 carbon atoms is developed. Single crystal analyses reveal that SAMs with shorter spacers exhibit stronger intermolecular interactions and denser packing. The molecular conformation of SAMs significantly impacts their molecular footprint and coverage on ITO. These factors result in the highest coverage of 2Cl‐2PACz and the lowest coverage for 2Cl‐3PACz on ITO. OSCs based on PM6:L8‐BO with 2Cl‐2PACz as HTL achieved high efficiencies of 18.95% and 18.62% with and without methanol rinsing of the ITO/SAMs anodes, corresponding to monolayer and multilayer structures, respectively. In contrast, OSCs utilizing the other SAMs showed decreased efficiencies as spacer length increased. The superior performance of 2Cl‐2PACz can be attributed to its shorter spacer, which reduces series resistance, hole tunneling distance, and barrier. This work provides valuable insights into the design of SAMs for high‐performance OSCs.